The Role of Community Service in Improving Educational Character of Students in a Boarding School in Yogyakarta - Ahmad Mufit Anwari (Publindo Akademika, 2022)
This study is to find out what activities carried out by boarding school to improve the character of the community in the boarding school environment by taking a case study in a boarding school in Yogyakarta. This research uses a type of field research that uses a qualitative approach. From the results of the analysis to examine the role of Islamic boarding schools to improve character in the Krapyak Islamic boarding school community in Yogyakarta, boarding school activities related to the community to improve the character of the people living in boarding schools are like community service. It can be concluded that the Krapyak Islamic boarding school in Yogyakarta has a role in the community around the boarding school.